Balanced Nutrition Education for Pregnant Women and Mothers Under Five in Efforts to Prevent Stunting: Balanced Nutrition Education for Stunting Prevention - Nurhidaya Nurhidaya; Dwi Ghita (CV. Paperhome Indonesia, 2026)
Exclusive breastfeeding remains a key strategy to improve infant health and reduce morbidity and mortality; however, its coverage is still suboptimal in several remote regions of Indonesia, including Yahukimo Regency, Papua Mountains. Antenatal classes are designed to improve maternal knowledge, skills, and confidence in preparing for childbirth and infant care, including breastfeeding practices. This study aimed to examine the association between active participation in antenatal classes and exclusive breastfeeding practices at Aplim Community Health Center, Yahukimo Regency. This research employed a quantitative analytical design with a cross-sectional approach. The population consisted of mothers with infants aged 6–12 months within the working area of Aplim Community Health Center. A total sampling technique was used, resulting in 30 respondents who met the inclusion criteria. Data were collected using a structured questionnaire assessing maternal characteristics, level of participation in antenatal classes, and exclusive breastfeeding practices during the first six months of life. Active participation was defined as attending at least three sessions and engaging actively during discussions. Data were analyzed using the Chi-square test with a significance level of 0.05. The results showed that among 19 mothers categorized as active participants, 18 (94.7%) practiced exclusive breastfeeding. In contrast, among 11 mothers categorized as inactive, only 2 (10.0%) provided exclusive breastfeeding. Statistical analysis indicated a significant association between active participation in antenatal classes and exclusive breastfeeding (p < 0.001). In conclusion, active participation in antenatal classes is significantly associated with higher likelihood of exclusive breastfeeding. Strengthening maternal engagement in antenatal education programs may contribute to improved breastfeeding outcomes in remote and underserved areas.